Low-temperature study of neutral and charged excitons in the large-area monolayer WS2. (11th May 2018) - Gu, Hong; Chen, Le; Lu, Youming; Tian, Feifei; Zhang, Zhiqiang; Xu, Ke; Wu, Jing; Botcha, V. Divakar; Li, Kuilong; Liu, Xinke
Abstract: We present a low-temperature optical study of the large-area monolayer WS2 grown by chemical vapor deposition (CVD). Power-dependent photoluminescence (PL) measurements were conducted, and temperature-dependent PL spectra were measured in the range of 3 to 300 K. With the comparative PL bands obtained, a stronger trion emission in the edge region was detected to be the key difference. Sulfur vacancies (SVs) were observed to increase in density along the growth direction and found to be the main source of the large population of local charge carriers. The monolayer WS2 exhibited an upper bound for the trion binding energy of 18 meV in the edge region.